LEGAL SIGNIFICANCE OF THE RESULTS OF RAPID SEARCH ACTIVITY THE IN EXPOSING OF CRIMES THE REPUBLIC OF UZBEKISTAN - Karabaev Oybek Ravshanovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the operational search activities in the Republic of Uzbekistan the use of information and material items obtained during the activities carried out by the implementing agencies as evidence in the course of the investigation was studied.